PENGARUH PRODUK DOMESTIK REGIONAL BRUTO (PDRB) DAN INVESTASI TERHADAP PENYERAPAN TENAGA KERJA DI KOTA MEDAN - Siska Magdalena; Noni Rozaini (Fakultas Ekonomi Universitas Negeri Medan, 2022)
Economic development has an important goal, one of which is to pursue job growth, so that there are sufficient job opportunities to realize this goal. This study aims to examine the involvement of GRDP and investment in employment, especially in the city of Medan. This study uses a quantitative type and data acquisition comes from Time Series from 2001 to 2020. The secondary data used in this study comes from the Central Bureau of Statistics of North Sumatra which is used as a source of data in the study, using E-views9 and using regression analysis. multiple linear for data processing.The study obtained results where the GRDP variable had a positive and significant effect on employment in the city of Medan having a result of 0.000 in its significance level. While the significance value of investment to employment is 0.1856, this means that it is positive but not significant. As for the third variable, it has a significance value of 87.65 percent to the absorption of labor in the city of Medan.Keywords : GRDP, Investment, and Labor Absorption